ANALISIS ELEMEN METALINGUISTIK BERBASIS ETNOPUITIKA PADA MAHASISWA PGSD - Nurhayati, Eni; Kisyani Laksono; Didik Nurhadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research explores the use of metalinguistic elements in ethnopoetics as a strategy to increase students' language awareness, particularly among PGSD students at PGRI Delta University. By combining linguistic and cultural aspects, this approach aims to provide a holistic understanding of language and improve the ability to analyze and use language in a multicultural context. The research method used is qualitative with data collection techniques through structured observation. The results showed that metalinguistic elements, such as phonology, morphology, syntax, semantics, and pragmatics, can be applied in learning Indonesian in elementary schools. This helps PGSD students in teaching local cultural values and improving students' communication skills. The implementation of these metalinguistic elements contributes to increased language awareness, reading and writing ability, and more effective communication skills. This research highlights the importance of understanding language as a means of communication and cultural expression, and how metalinguistic elements can help students understand oral traditions and social values. The integration of metalinguistic elements in learning not only enhances students' learning experience but also prepares them to become better communicators.